2021
DOI: 10.1021/acs.orglett.1c03693
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Trimerization of Isocyanides: De Novo Synthesis of 2-Indole-Substituted Quinolines and Pyridines

Abstract: A catalyst-free chemoselective trimerization reaction of readily available isocyanides is described. This domino reaction provides facile access to a wide range of 2-(indol-2-yl)-quinolines and 2-(indol-2-yl)-pyridines in moderate to excellent yields. A “head to head” heterodimerization of two isocyanides is proposed as the key step of this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…published the first report of chemoselective trimerization of isocyanides 275 with 304 and 309 for the synthesis of 2‐(indol‐2‐yl)‐quinolines 308 and 2‐(indol‐2‐yl)‐pyridines 310 in DME at 150 °C (Scheme 41). [19] Under these catalyst‐free conditions, two molecules of isocyanides 275 react with one molecule of isocyanides 304 to produce 2‐(indol‐2‐yl)‐quinolines 308 in moderate to excellent yields (60–96%). However, the reaction of the two isocyanides 275 molecules with isocyanides 309 instead, affords 2‐(indol‐2‐yl)‐pyridines 310 in good to excellent yields (78–98%) under the same circumstances.…”
Section: Oligomerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…published the first report of chemoselective trimerization of isocyanides 275 with 304 and 309 for the synthesis of 2‐(indol‐2‐yl)‐quinolines 308 and 2‐(indol‐2‐yl)‐pyridines 310 in DME at 150 °C (Scheme 41). [19] Under these catalyst‐free conditions, two molecules of isocyanides 275 react with one molecule of isocyanides 304 to produce 2‐(indol‐2‐yl)‐quinolines 308 in moderate to excellent yields (60–96%). However, the reaction of the two isocyanides 275 molecules with isocyanides 309 instead, affords 2‐(indol‐2‐yl)‐pyridines 310 in good to excellent yields (78–98%) under the same circumstances.…”
Section: Oligomerizationmentioning
confidence: 99%
“…Compared to the popularity of single isocyanide reactions, few examples of reactions involving two/multiple isocyanides have been reported in literature. Two molecules of isocyanide carry out reactions such as double isocyanide insertions, [16,17] isocyanide‐based MCR [18] and oligomerization [19] /polymerization [15] . However, few reports have been disclosed on double isocyanide insertions because isocyanides are readily polymerized under metal‐catalyzed conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A fascinating chemoselective trimerization reaction of isocyanides for synthesis of 2-(indol-2-yl)quinolines and 2-(indol-2-yl)-pyridines was accomplished by Dong, Xu and co-workers. 112 The authors found that the reaction of aryl isocyanides 172 and o -alkenyl arylisocyanides 173 in 1,2-dimethoxyethane (DME) at 150 °C selectively produced 2-(indol-2-yl)quinolines 174 . On the other hand, the assembly of aryl isocyanides 172 and 1,3-dienyl isocyanides 175 yielded trimerized product 2-(indol-2-yl)-pyridines 176 under similar reaction conditions.…”
Section: Uncatalyzed/thermally Assisted Synthesismentioning
confidence: 99%
“…4 In recent years, many domino and multicomponent reactions based on the nucleophilic addition of alkyl isocyanides have been successfully developed. 5…”
Section: Introductionmentioning
confidence: 99%